Periodontal Tissue Engineering: A Literature Review: Life Sciences -Dentistry - Salian, Dr. Shrishti; V. Dhadse, Dr. Prasad; Patil, Dr Ruchita (International Journal of Life Science and Pharma Research, 2023)
Periodontal regeneration is the formation of new cementum, periodontal ligament, and alveolar bone followingperiodontal surgery. It is widely believed that tissues formed during regeneration are more resistant to deterioration than thosegained when healing occurs through repair, which is why regeneration is so important. The two main goals of periodontal therapyare controlling the infection and rebuilding the architecture and function of periodontal tissues. Due to the periodontium's highlyhierarchical organization, which calls for a highly coordinated spatiotemporal healing response to enable regeneration, theregeneration of the periodontal apparatus with the formation of the bone-PDL-cementum complex at the same time continues topresent challenges. The final goal of periodontal therapy for tissues destroyed by periodontal diseases is the regeneration of theattachment apparatus, composed of the development of new alveolar bone, periodontal ligament, and cementum. With a clearunderstanding of the periodontal disease process, the regeneration of the periodontium is one of the major goals of periodontaltherapy. This review is an update on the current tissue engineering knowledge as a possible periodontal regeneration technique.